Keterampilan Kader Dalam Deteksi Dini Masalah Gizi Balita Di Posyandu Desa Jambuwok Kecamatan Trowulan Mojokerto - Aminatus Zahro , Nursaidah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2013)
Monitoring of nutrition has not run as expected, due to public awareness of the role of cadres and the existence of posyandu still far from expectations. The purpose in this study to determine the skills of cadres in the early detection of nutrition problems in the Village District Jambuwok Trowulan Mojokerto district. This study is a descriptive study. The variables in this study are the skills of cadres in the early detection of nutrition problems in which the population in this study as many as 25 cadres, the sample in this study took all the members of the population as much as 25 cadres of the sampling technique using saturation sampling. By using a check sheet lists the research instrument that was held on 7 May to 7 June 2012. Based on the result showed that the average - average unskilled cadres in the early detection of nutrition problems in Posyandu as many as 19 cadres (76%) is observed from the age of the respondents can be seen that 68% of 20-35 year-old cadres, cadres of the majority of 52% high school educated, and 88% in terms of job most of the respondents did not work. To obtain a more meaningful explanation researchers create cross tabulation between the general characteristics of the skills of cadres. Cross tabulation of the results can be seen that the majority of respondents are skilled high school educated, and respondents aged 20-35 years did not work. Conclusion that village cadres Jambuwok District Trowulan Mojokerto District average - average unskilled cadres. Health care workers should provide such training lectures, group discussions, demonstrations, case studies, problem-solving.